Post-stroke dysphagia: A review and design considerations for future trials. Issue 4 (June 2016) - Cohen, David L; Roffe, Christine; Beavan, Jessica; Blackett, Brenda; Fairfield, Carol A; Hamdy, Shaheen; Havard, Di; McFarlane, Mary; McLauglin, Carolee; Randall, Mark; Robson, Katie; Scutt, Polly; et al.
Post-stroke dysphagia (a difficulty in swallowing after a stroke) is a common and expensive complication of acute stroke and is associated with increased mortality, morbidity, and institutionalization due in part to aspiration, pneumonia, and malnutrition. Although most patients recover swallowing spontaneously, a significant minority still have dysphagia at six months. Although multiple advances have been made in the hyperacute treatment of stroke and secondary prevention, the management of dysphagia post-stroke remains a neglected area of research, and its optimal management, including diagnosis, investigation and treatment, have still to be defined.